PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MASALAH DENGAN JAS MATERI PENCEMARAN LINGKUNGAN DI SMP (Journal of Innovative Science Education, 2014)
AbstrakTujuan penelitian ini adalah mengembangkan perangkat pembelajaran ber- basis masalah dengan pendekatan JAS dan menguji keefektivan pembelaja- ran  berbasis masalah dengan pendekatan JAS dalam menumbuhkan sikap peduli lingkungan. Pengembangan perangkat menggunakan model 4-D Thiagarajan yang telah dimodifikasi, terdiri dari define, design, dan develop. Perangkat pembelajaran yang dikembangkan meliputi silabus, RPP, bahan ajar, LKPD dan alat evaluasi. Perangkat pembelajaran yang dikembangan berkategori sangat efektif, karena dapat menumbuhkan aktivitas 90% (san- gat baik), minat 100%( sangat berminat), sikap 86,7% (sangat baik), respon 93,33% (sangat senang), keterampilan 86,7% (sangat baik) dan mening- katkan hasil belajar dengan ketuntasan 96,7%, serta dapat menumbuhkan sikap peduli lingkungan dengan   katagori sangat peduli  sebesar 100 %., dengan rentang nilai 83,33 s.d 100. Hasil analisis regresi ada korelasi yang signifikan antara hasil belajar kognitif dengan sikap peduli lingkungan.AbstractThe research objectives are to develop teaching learning material based on the prob- lem by using JAS approach about the topic environmental pollution and to examine how effective teaching problem based learning by using JAS approach in the topic of  environmental pollution encouraging students’ attitude to care of  environment. The development of material uses Thiagarajan 4-D model which has been modified. It consists of define, design, and develop. Teaching learning material which is deve- loped includes syllabus, lesson plan, instructional material, LKPD and evaluation form. It can be stated that teaching learning material has been developed is very ef- fective. Because it can increase students’ activities to 90%, means very good, students’ interest 100%, means very interested, students’ attitude to 86.7%, means very good, students’ response to 93.33%, means very enthusiastic, students’ skill to 86.7%, me- ans very good and increase students’ learning result  to 96.7% of the completeness learning result and encourage students’ care of  environment to 100%, means very high , with passing grade of 83.33 to 100. The analysis regressive result is significant correlation between cognitive learning result and the attitude of environmental care.